2018
DOI: 10.1371/journal.pone.0197474
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct antibody administration with standard treatment reduces relapse rates in a murine tuberculosis model of necrotic granulomas

Abstract: Matrix metalloproteinase (MMP)-9 is a zinc-dependent protease associated with early immune responses to Mycobacterium tuberculosis infection, macrophage recruitment and granuloma formation. We evaluated whether adjunctive inhibition of MMP-9 could improve the response to standard TB treatment in a mouse model that develops necrotic lesions. Six weeks after an aerosol infection with M. tuberculosis, C3HeB/FeJ mice received standard TB treatment (12 weeks) comprising rifampin, isoniazid and pyrazinamide alone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
(47 reference statements)
0
22
0
Order By: Relevance
“… 23 , 24 Various MMP inhibitors have been used to study the immunomodulatory role of MMPs in Mtb infection and showed promising effect. 25 , 26 For example, Xu et al reported that inhibition of matrix metalloproteinase (MMP) enhances the in vivo potency of isoniazid and rifampicin. 27 In summary, our results revealed a series of processes and pathways related to Mtb infection, which provide a new basis for further explore the pathogenesis of ATB.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Various MMP inhibitors have been used to study the immunomodulatory role of MMPs in Mtb infection and showed promising effect. 25 , 26 For example, Xu et al reported that inhibition of matrix metalloproteinase (MMP) enhances the in vivo potency of isoniazid and rifampicin. 27 In summary, our results revealed a series of processes and pathways related to Mtb infection, which provide a new basis for further explore the pathogenesis of ATB.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the cipemastat-treated group had a trend toward worse cavitary disease. Ordonez et al used cipemastat monotherapy in the C3HeB/FeJ mouse model that develops cavitary lesions after aerosol infection with Mtb [117]. Similar to rabbits, cipemastat-treated mice had worse cavitation and more disease severity compared to controls.…”
Section: Treatmentmentioning
confidence: 99%
“…Marimastat also reduced vascular leakage surrounding TB granulomas and increased the concentration of isoniazid in Mtb -infected lungs compared to controls. Similarly, targeting MMP-9 with a specific antibody in addition to anti-TB therapy (rifampin, pyrazinamide, and isoniazid) reduced pulmonary bacterial burden and significantly lowered relapse rates in a cavitary mouse model of pTB [117]. Therefore, MMP inhibition in conjunction with antibiotic therapy may be beneficial, whilst MMP inhibition monotherapy seems to be harmful, further demonstrating the complexity of events in vivo and the importance of performing translational preclinical studies that most closely reflect the intended therapeutic use in patients.…”
Section: Treatmentmentioning
confidence: 99%
“…In this model, mice can develop necrotic caseous lung lesions with a significant extracellular bacterial population and even lung cavities (7, 2224, 3135). The standard TB treatment regimen performs similarly in this model as in the BALB/c model (9, 22, 3638), thus allowing for the specific evaluation of clofazimine and rifapentine activity in this disease setting.…”
Section: Introductionmentioning
confidence: 99%